“First of all, don’t be afraid”: Traditional midwifery during the COVID-19 pandemic in Mexico - Costa da Silva, Sislene (2025)
This article recounts the experiences of traditional Mayan midwives linked to the Organization of Indigenous Doctors of the state of Chiapas, who live in the region of Los Altos. The objective was to observe the way midwives acted during the COVID-19 pandemic, considering that in their role as traditional doctors they possess a great wealth of knowledge, therapies, and care. During the pandemic, there was significant demand for their services in the communities, even among people who did not usually go to them. In the face of the health crisis, midwives assumed important roles. They did not stop caring for pregnant women and their babies and they provided emotional support to affected families and communities. Without support from the state, they used their knowledge of healing and care based on their sense of the Mayan world and their life experiences. Methodologically, I used listening, observation, and feeling alongside the coordinator of women and midwives and her son. Their words constitute political philosophies in a triangulated relationship between mother-child-researcher. It is concluded that the situations portrayed in the article summon us to think about alternative worlds or ways of continuing to live from the centrality of everyday politics, based on the reproduction of life and accompaniment among women.